Clinical Pharmacogenetics Implementation Consortium (CPIC) Guideline for Pharmacogenetics‐Guided Warfarin Dosing: 2017 Update. Issue 3 (4th April 2017) - Johnson, JA; Caudle, KE; Gong, L; Whirl‐Carrillo, M; Stein, CM; Scott, SA; Lee, MT; Gage, BF; Kimmel, SE; Perera, MA; Anderson, JL; Pirmohamed, M; et al.
Abstract : This document is an update to the 2011 Clinical Pharmacogenetics Implementation Consortium (CPIC) guideline for CYP2C9 and VKORC1 genotypes and warfarin dosing. Evidence from the published literature is presented for CYP2C9, VKORC1, CYP4F2, and rs12777823 genotype‐guided warfarin dosing to achieve a target international normalized ratio of 2–3 when clinical genotype results are available. In addition, this updated guideline incorporates recommendations for adult and pediatric patients that are specific to continental ancestry.